Integral HOMFLY-PT and sl(𝑛)-Link Homology - Daniel Krasner (International Journal of Mathematics and Mathematical Sciences)
Using the diagrammatic calculus for Soergel bimodules, developed by Elias and Khovanov, as well as Rasmussen's spectral sequence, we construct an integral version of HOMFLY-PT and sl(𝑛)-link homology.